Perception of Elementary School Students on the Tsunami Early Warning System (TEWS) in High-Risk Tsunami Zones in Padang City - Affifa Syah Raudhatul Jannah; Eka Juliafad (CIVED, 2025)
This study aims to understand students' perceptions of the Tsunami Early Warning System (TEWS) in tsunami-prone areas, focusing on SD Pertiwi 2 in Padang City. TEWS is crucial in disaster risk mitigation as it provides early warnings to reduce casualties during a tsunami. This research utilizes a quantitative descriptive approach, with a questionnaire distributed to 69 sixth-grade students. The findings reveal that 85.51% of students understand TEWS, 97% believe TEWS is essential for safety, yet only 63% are aware of a TEWS installation near their school. These results indicate a need for enhanced local education about TEWS, particularly by schools and relevant agencies.